ZENONAS NORKUS, ON BALTIC SLOVENIA AND ADRIATIC LITHUANIA - Fabrykant, Marharyta (Baltic Journal of Political Science, 2015)
Several years ago, the 20th anniversary of the fall of Communism prompted a considerable number of academic meetings and publication. By that time, most ex-communist states had already made their new identities clear and familiar to the world – or so it seemed. Transitology was slowly growing out of intellectual fashion, and the whole region affected by the post-communist transformation was more and more frequently regarded as stable and comparatively uninteresting. Amid this fading interest, conferences that aimed to re-examine of the post-communist transition were considered, even by the participants themselves, more of a ritual commemoration than a necessary attempt to solve pressing issues.